PSVI-25 Inclusion of Lemna as a plant-based protein ingredient in dog and cat diets. (30th November 2020) - Panasevich, Matt; Frantz, Nolan; Reinhart, Greg
Abstract: Our objective was to evaluate the inclusion of a novel plant-based protein (Lemna; MC Select; Parabel ® ; Vero Beach, FL) in dog diets at 0, 5, and 10% and cat diets at 0, 10 and 15% for palatability, stool quality, and nutrient digestibility. We hypothesized that Lemna would be a viable protein source in both cat and dog diets by showing no detriments to nutrition outcomes. All feeding tests were conducted at an independent research facility (Susquehanna, PA). A standard 2 bowl palatability test over a 2-day period was done with adult dogs and cats (n = 30 each) to determine intake ratios (IR) between test diets (Lemna -containing diets) and control (0% Lemna) diet. Total tract nutrient digestibility was conducted with 18 adult dogs and 21 adult cats (n=6–7 per diet) with 5 days of diet acclimation followed by 5 days of total fecal collection. Stool quality was evaluated on a 1–5 scale where 1= non-formed/diarrhea and 5= hard, formed. Palatability data was analyzed via Wilcoxon Signed Rank, and digestibility and stool quality data were analyzed by ANOVA with a Tukey's post-hoc means separation (SAS version 9.4). Intake ratios in cats between 10% Lemna and control were significantly (P < 0.05) in favor of control, while no difference was observed between 15% Lemna and control. For dogs, 5% and 10% Lemna had significantly (P < 0.05) lower IR demonstrating a preference to control. Both cats and dogs fed Lemna diets had acceptable stool quality (3.42 avg for cat and 3.34 avg for dog). No detriments in nutrient digestibility were observed in dogs fed 5% and 10% Lemna; however, cats fed 10% and 15% Lemna had significantly (P < 0.05) lower dry matter, protein, and energy digestibility versus control. In conclusion, these data suggest more development is needed for Lemna inclusion in companion animal diets. Thursday, July 23, 2020